Advancing green technology: demulsifier preparation and evaluation for crude oil emulsion treatment using corn oil - Abed, Mohammed M.; Naife, Tariq M.; Abdel Kawi Ibrahim, Mervat Amin (Iraqi Journal of Chemical and Petroleum Engineering, 2024)
Globally, oil production has steadily increased which causes a rise in the coproduction of oil and water emulsions. These emulsions pose significant challenges in transportation and the oil refinery industry, causing high-pressure drops and corrosion problems due to chlorides in the water. Despite advancements in renewable energy, crude oil remains a primary energy source. The crude oil industry faces numerous challenges, including cost emulsion issues. This study developed a corn oil bio-demulsifier (MFK). A unique demulsifier was tested using FTIR, GC-MS, and TGA. Using the bottle test method, the produced demulsifier MFK was tested with Basrah oil and East Baghdad S1 oil. The emulsion-breaking processes have been studied under several factors, such as settling time, dosage, temperature, pH, water content, and mixing time after demulsifier addition. At 2000 ppm Basrah oil, water separation efficiency reached 75%. For East Baghdad S1 oil, the highest separation result was 43.3% at 4000ppm, after 5 h of settling time at 70°C, with a 30/70 water-to-oil ratio. When studying the pH, the best water separation rate was 86.5% at a pH of 10. The best water content was 92% when the water-to-oil ratio was 50/50, and the best demulsifier mixing time with the emulsion was 2 min with a separation rate of 74.5%. When mixing was increased, undesirable results occurred. This study demonstrated that biodemulsifiers may replace conventional biodemulsifiers in early units while reducing environmental and economic impacts with further study and development.